2010
DOI: 10.1111/j.1743-6109.2009.01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Biomarker Analysis of Primary Peyronie’s Disease Cells

Abstract: Introduction The molecular pathogenesis of Peyronie’s Disease (PD) remains unclear more than 250 years after its initial description. Because of this, no test is currently available to accurately predict PD progression among those affected. Aim To investigate the expression of wound healing and fibrosis-associated proteins in primary cell cultures of PD fibroblasts to determine whether altered protein expression patterns can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 36 publications
2
26
0
3
Order By: Relevance
“…In 2010, De Young and coworkers, for the fi rst time, investigated the expression of wound healing and fi brosis-associated proteins in primary cell cultures of PD fi broblasts [ 18 ]. They showed that primary cell cultures from PD plaque displayed overexpression of several proteins that are established components of fi brosis and wound healing.…”
Section: The New Era Model: From Animals To Cell Culturementioning
confidence: 98%
See 2 more Smart Citations
“…In 2010, De Young and coworkers, for the fi rst time, investigated the expression of wound healing and fi brosis-associated proteins in primary cell cultures of PD fi broblasts [ 18 ]. They showed that primary cell cultures from PD plaque displayed overexpression of several proteins that are established components of fi brosis and wound healing.…”
Section: The New Era Model: From Animals To Cell Culturementioning
confidence: 98%
“…They showed that primary cell cultures from PD plaque displayed overexpression of several proteins that are established components of fi brosis and wound healing. In particular, they found that statistically signifi cant increases in smooth muscle alpha-actin, betacatenin, and heat-shock proteins (Hsp47) were identifi ed in cells derived from PD relative to cells derived from normal tunica albuginea tissue [ 18 ]. Moreover, they found changes in TGF-β1 receptor and fi bronectin in association with altered expression of additional as yet unidentifi ed proteins at 4.7, 8.9, 10.8, 16.8, and 76.8 kDa [ 18 ].…”
Section: The New Era Model: From Animals To Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In Peyronie's disease, regulated expression of certain proteins such as the alpha-actin, beta-catenin, and heat shock proteins (Hsp47), which are established components of fibrosis and wound healing [30] have been noted/recognized.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Newer investigative tools such as proteomic markers, cell-specific immunohistochemistry, western blot analyses and DNA microarray technology have also assisted in the functional and morphologic assessments as well as understanding of the pathophysiology of PD. 12,13 In the current article, existing English literature pertaining to the use of rodent models for the evaluation of PD is reviewed with primary focus on the development and application of these experimental animal and cell cultures models.…”
Section: Introductionmentioning
confidence: 99%